Phagocytosis in Teleosts. Implications of the New Cells Involved - María Ángeles Esteban; Alberto Cuesta; Elena Chaves-Pozo; José Meseguer (Biology, 2015)
Phagocytosis is the process by which cells engulf some solid particles to form internal vesicles known as phagosomes. Phagocytosis is in fact a specific form of endocytosis involving the vesicular interiorization of particles. Phagocytosis is essentially a defensive reaction against infection and invasion of the body by foreign substances and, in the immune system, phagocytosis is a major mechanism used to remove pathogens and/or cell debris. For these reasons, phagocytosis in vertebrates has been recognized as a critical component of the innate and adaptive immune responses to pathogens. Furthermore, more recent studies have revealed that phagocytosis is also crucial for tissue homeostasis and remodeling. Professional phagocytes in teleosts are monocyte/macrophages, granulocytes and dendritic cells. Nevertheless, in recent years phagocytic properties have also been attributed to teleost lymphocytes and thrombocytes. The possible implications of such cells on this important biological process, new factors affecting phagocytosis, evasion of phagocytosis or new forms of phagocytosis will be considered and discussed.